THE FIGURATIVE LANGUAGE SARCASM AND SATIRE ON THE SONG “WE CAN’T STOP” AND “WTF DO I KNOW” BY MILEY CYRUS AND “RECKLESS” BY MADISON BEER - Tiurmaya Agustina (Journal of Language, Literature and Teaching, 2022)
This research analyses the type of figurative language (sarcasm or mock; impoliteness is used to perform face threatening acts with the use of politeness strategies that are obviously insincere and thus remain surface relizations and satire; the desire to use precisely clear language to still an audience to protest which is intends to be describe painful or absurd situations or foolish or wicked persons or groups as vividly as possible ) used in the songs dominantly and the reasons of using figurative language (sarcasm and satire), which the songs composed of figurative language applied in literary works. As in the structure of language, figurative language is a component of  semantics as a way to express something that is not the actual meaning of the word. Commonly, figurative language is categorized by the terms; simile, metaphore, personification, hyperbole, innuendo, paradox, irony and so on. This research conducted with qualitative descriptive research design as a systematic action that covers gathering of data for the purpose of finding answer and or explanation about social issues  to describe the problem of the study. This research found the dominant figurative language (sarcasm and satire) on the song and the reasons of using it. Sarcasm and Satire are types of figurative language.Keywords : Figurative Language, Sarcasm, Satire, Literary, Song